Johnsongrass Mosaic Virus - Trucco, Veronica Milagros (2025)
Potyviruses are one of the largest plant virus groups infecting both monocot and dicot species and causing a negative economic impact on agriculture across the world. The potyvirus johnsongrass mosaic virus (JGMV) was initially considered a strain of other potyviruses until it was determined to be an independent virus through genomic sequencing studies. This chapter reviews the main aspects of JGMV, including its identification and focusing on taxonomic and biological properties as well as epidemiological aspects and control measures.